Enhancing Growth and Yield of Caisim Mustard (Brassica juncea L.) in Hydroponic Cultivation through Trichoderma Consortium and ABmix Combination: Meningkatkan Pertumbuhan dan Hasil Sawi Caisim (Brassica juncea L.) dalam Budidaya Hidroponik melalui Kombinasi Konsorsium Trichoderma dan ABmix - Gumelar, Fadillah Timur; Sutarman, Sutarman (Indonesian Journal of Innovation Studies, 2023)
This research aims to investigate the impact of Trichoderma application, both individually and in combination with ABmix and shrimp pond water, on the growth and yield of caisim mustard plants in a hydroponic system. The study was conducted in Tlocor Village, Jabon District, Sidoarjo Regency, from November to December 2022, using a Randomized Block Design (RBD) with 6 repetitions. The treatments comprised various nutrient combinations: 100% ABmix, Trichoderma and husk dilution, Trichoderma and pond water dilution (one-third of water medium), 50% ABmix with Trichoderma and husk dilution, and 50% ABmix with Trichoderma and pond water dilution. Data were analyzed using variance at 5% and 1% levels, followed by a 5% BNJ test. The findings indicated that a 50% concentration of Trichoderma combined with ABmix significantly increased plant height, leaf count, and leaf area up to 28 days after planting. Furthermore, it enhanced harvested wet weight, harvested dry weight, and harvest index. Notably, Trichoderma applied with one-third shrimp pond water as a planting medium resulted in the highest growth with 9.38 leaves, 109.23 cm2 leaf area, and harvested wet and dry weights of 68.25 and 11.00 g per plant. Overall, the Trichoderma consortium demonstrated the potential to effectively enhance the growth and yield of caisim mustard, offering a promising alternative to chemical nutrients in hydroponic cultivation. Highlights: Effectiveness of Trichoderma: The study aimed to determine the effect of Trichoderma application and its combination with ABmix and shrimp pond water on the growth and yield of caisim mustard plants in a hydroponic system. Results showed that the application of Trichoderma significantly increased plant height, number of leaves, and leaf area up to 28 days after planting. Optimal Nutrient Combination: The study found that using a combination of Trichoderma and ABmix at a concentration of 50% resulted in the highest increase in harvested wet weight, harvested dry weight, and harvest index. Additionally, using one-third of shrimp pond water for planting media produced the highest growth. Potential of Trichoderma Consortium: The study suggests that Trichoderma has the potential to effectively increase the growth and production of mustard greens in hydroponic cultivation. It could also be a viable substitute for chemical nutrients, promoting environmentally friendly and sustainable farming practices. Keywords: ABmix Combination, Caisim Mustard, Growth Enhancement, Hydroponic Cultivation, Trichoderma Consortium